Kinetic-Thermodynamic Promotion Engineering toward High-Density Hierarchical and Zn-Doping Activity-Enhancing ZnNiO@CF for High-Capacity Desalination - Ma, Jie; Xing, Siyang; Wang, Yabo; Yang, Jinhu; Yu, Fei (Nano-Micro Letters, 2024)
Despite the promising potential of transition metal oxides (TMOs) as capacitive deionization (CDI) electrodes, the actual capacity of TMOs electrodes for sodium storage is significantly lower than the theoretical capacity, posing a major obstacle. Herein, we prepared the kinetically favorable ZnxNi1 − xO electrode in situ growth on carbon felt (ZnxNi1 − xO@CF) through constraining the rate of OH− generation in the hydrothermal method. ZnxNi1 − xO@CF exhibited a high-density hierarchical nanosheet structure with three-dimensional open pores, benefitting the ion transport/electron transfer. And tuning the moderate amount of redox-inert Zn-doping can enhance surface electroactive sites, actual activity of redox-active Ni species, and lower adsorption energy, promoting the adsorption kinetic and thermodynamic of the Zn0.2Ni0.8O@CF. Benefitting from the kinetic-thermodynamic facilitation mechanism, Zn0.2Ni0.8O@CF achieved ultrahigh desalination capacity (128.9 mgNaCl g−1), ultra-low energy consumption (0.164 kW h kgNaCl−1), high salt removal rate (1.21 mgNaCl g−1 min−1), and good cyclability. The thermodynamic facilitation and Na+ intercalation mechanism of Zn0.2Ni0.8O@CF are identified by the density functional theory calculations and electrochemical quartz crystal microbalance with dissipation monitoring, respectively. This research provides new insights into controlling electrochemically favorable morphology and demonstrates that Zn-doping, which is redox-inert, is essential for enhancing the electrochemical performance of CDI electrodes. Highlights: 1 Through facial basicity adjustment, kinetically favorable ZnxNi1-xO@CF electrode was formed with a high density hierarchical structure and three dimensional open pores. 2 The optimal Zn-doping ratio in ZnxNi1-xO@CF has excellent sodium storage and desalination performance (128.9 mg g-1). 3 The mechanism of Na+ intercalation process was studied by electrochemical quartz crystal microbalance with dissipation monitoring in situ test and the activation mechanism of redox-inert Zn-doping on electrode materials was reported.